Virtual Teams' Research Between 2019 And 2021: A Systematic Review of The Literature - Filipa FERREIRA; Ana Cláudia RODRIGUES (Communications of International Proceedings, 2023)
This article performs systematic literature on virtual teams’ research, following the structure of the article "Virtual Teams: Thematic Taxonomy, Constructs Model and Future Research Directions," which focuses on the period between 2007 and 2018 prepared by Alaid, Alnsour, and Alsharo. The present study extending the analysis to three more years, between 2019 and 2021, aims to understand the evolution of the study of virtual teams and thus unveil the impact that the COVID-19 pandemic had on the subject. The methodology used was a systematic review of the literature using the methodology proposed by Ramey and Rao, the same used in the article mentioned above. The review came up with 18 articles, which we analyzed according to the type of variables. The review showed seven categories of independent variables, culture being the most frequent category, which is an emergent category, inexistent in the previous study. There were six categories of dependent variables, among them performance the most prominent, as in the previous study period. There were fewer moderator variables in the present study and emerged mediator variables that were not present in the reference study. The findings point to a higher complexity of the research conducted between 2019 and 2021: the emergence of mediating variables and several studies within the same research plan. To better understand the data collected, we organized the independent and dependent variables into dimensions, facilitating the analysis and adding to the presentation of findings contributing to enlightening future research on the most recent research constructs studied on VT.
Keywords: Systematic literature review; Virtual teams; Covid-19 pandemic